Isolation and properties of a feruloyl esterase from Aureobasidium pullulans and its mechanism in lignocellulose degradation - Rumbold, Karl, 1973- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2003.